Inovações educacionais presentes no PNAIC - Cichocki, Manoela Soares (2018)
This research approaches the perception of a group of teachers of Elementary School of city of São José dos Pinhais (Paraná), about the innovations proposed in the PNAIC (Pacto Nacional de Alfabetização na Idade Certa – National Agreement of Literacy in Certain Age). It is a qualitative, exploratory and analytic research, whose principal objective consists in identify the implemented innovations on the pedagogical practices in this group of literacy professors, which participated of the Formation Program PNAIC between the years of 2013 and 2016. By the literature review, this Program relies in a group of principles, as well as 4 acting axis: continuous formation of the literacy teachers that act in the 1ft, 2sd and 3td years of Elementary School; didactic materials; systematic evaluations; and management, social control and mobilization. The principles are: the alphabetical write‟s system is complex and demands a systematic and challenging teaching; the reading and writing capacity‟s development occurs during the entire education process, but must start soon in the beginning of Basic Education; knowledge provided from different areas could and must be appropriated for children, so that they can hear, talk, read, white about different topics and act in society; the playfulness and children‟s beware are basic conditions in the teaching and learning‟s process (BRASIL, 2012a, p.27). The literacy professor is considered essential to the PNAIC‟s success, once its practical is the way to realize the Program‟s objectives. In this dissertation, the text contemplates three chapters. The first explores questions related to innovation and educational challenges‟ concepts, and how they occur in the pedagogical practices. For this, we bring to the dialog authors like Fullan (2009), Correia (2000), Hernandez (2012), Carbonell (2002), Cardoso (1992), Messina (2001) and Walter Garcia (1995). The second chapter approaches the PNAIC‟S proposal and principles and the teacher‟s role in the same proposal. We describe, also, each of the formation phases, as well as the materials and content that were used by the professors during the proposal. Besides, we bring the teachers‟ views about the program‟s proposal and implementation. To this chapter were used documents from MEC (1998) (2012) (2014) (2015) and (2016), and authors like Cichocki (2016), Foragi (2013), Joe Garcia (2016), Martimiano (2013) and Souza (2007). Another chapter presents the methodological procedures of the research. We describe the data collection, during which were obtained the research‟s data, by means of questionnaires and semistructured interviews, next to literacy teachers who participate of the continuous formation in the city of São José dos Pinhais. The interviews content‟s analyze was based on the Bardin‟s method (2016). This possibilities the creating of the following categories of interpretative‟s analyze: modify the teacher’s thought, teaching strategies and ways of thinking. In the last section of the text, we introduce some considers about the realized investigation and point possible research‟s contributions regarding to training teachers.